What is pain: Are cognitive and social features core components? - Kenneth D. Craig; Nicole E. MacKenzie (Wiley, 2021)
Abstract Pain is a universal experience, but it has been challenging to adequately define. The revised definition of pain recently published by the International Association for the Study of Pain addressed important shortcomings of the previous version; however, it remains narrow in its focus on sensory and emotional features of pain, failing to capture the substantial roles of cognitive and social core components of the experience and their importance to advances in pain management. This paper reviews evidence and theoretical models for the significant role social and cognitive factors play in pain experience and we argue that without explicit recognition of these core components in the definition, significant nuances are lost at a cost to understanding and clinical management of pain. A focus on sensory and emotional features perpetuates biomedical interventions and research, whereas recognition of cognitive and social features supports a multidimensional model of pain, advances in interdisciplinary care, and the benefits of cognitive behavioral therapy and self‐management interventions. We also explore the six Key Notes that accompany the new definition of pain, discuss their application to the understanding of pain in childhood, and, in doing so, further explore social and cognitive implications. Considerations are also described for assessment and treatment of pain in pediatric populations.